DIFFERENT VIEWS ON THE POSITION AND ROLE OF THE PROTECTOR OF THE CITIZEN REPUBLIC OF SERBIA - Petković, Dragana S; Milošević, Vladimir D. (NBP. Nauka, bezbednosti, policija, 2018)
The first law on the Protector of the Citizens in the Republic of Serbia was passed in 2005, in order to retire certain changes in 2007 to comply with the Constitution of Serbia. The position and role of Protector of the Citizens in the legal system of the Republic of Serbia are defined by the 2006 constitution of the Republic of Serbia. The position, role, choice, jurisdiction and behavior of the Protectors of the Citizens of the RS are regulated based on the characteristic features of the Ombudsman of the countries in the region with certain modalities. Regarding the position and role, the institution of the Protector of the Citizens of the RS was made based on the Danish model, but some modern solutions were added. The normative regulation of the jurisdiction and position of the Protector of the Citizens deserves detailed processing, with a special review of the legal practice with the aim of examining the proposal de lege ferendi of the amendment of legal regulation. In his short ten-year history, the Protector of the Citizens of the RS applying and developing the various powers through various and diverse procedures and in different fields of action. With the help of the symbiosis of the normative and the experiential, the authors intend to point out of necessary legal changes and the way that the further evolution of this young institution in our legal system could be direct.